Hubungan Intensitas Kebisingan dan Keluhan Subyektif Gangguan Pendengaran Pengguna Studio Musik di Gunungkidul Tahun 2010 - Dhamas Sigit Prasetya; Siti Hani Istiqomah; Abdul Hadi Kadarusno (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
Noise is hearing sensation which pass through the ear and is caused by air pressure deviation. This deviation is usually produced by vibrating or beaten things like guitar strings or drums. High noise level inside music studios can cause some health problems such as fatigue, communication disorder, blood pressure decrease, and some hearing disturbances. The maximum treshold of noise is 85 dB. The study is aimed to understand the relationship between noise intensity and subjective complaint on hearing disturbance among music studio users. This descriptive study used cross sectional survey approach and observed 100 music studio users in Gunungkidul regency. The data was analysed by using chi-square test with 95% degree of confidence, and shows that there are relationship between the variables (p<0,001). It is advised that the musicians should give more attention to use ear protector, such as ear plug for reducing the risk of getting hearing problems.